Turbidite-hosted gold deposits - Leeming, Prudence Mary (Rhodes University, Faculty of Science, Department of Geology, 1985)
Turbidite-hosted gold deposits contribute a significant proportion to world lode gold production and have also provided substantial gold to alluvial resources. Turbidity current deposits occur throughout geological time within Archaean greenstone belts, Proterozoic orogenic belts and rifted passive continental margins, and Palaeozoic geosynclines. Representing the end member of the sedimentary cycle, turbidites have the attribute of preservation not only on an individual bed basis but also due to below wave base accumulation in submarine deeps. Cyclic deposition according to the Bouma sequence punctuates turbidite deposition by a series of diastems. Accumulation of organic, pelagic and chemical sediments may concentrate gold to protore enrichment levels i n a primary sedimentary environment. Dewatering during diagenesis and low-grade metamorphism under reducing conditions may redistribute gold with transport as low energy organo- and thio-complexes. Gold may precipitate with diagenetic pyrite and silica near black shale and/or partially replace fine carbonate detritus. Gold solubility increases with high grade amphibolite facies metamorphism (T 400ÂºC) when efficient leaching of gold and transport by simple chloro- and hydroxychloro - complexes to lower greenschist regions takes place. Reduced permeability of turbidite strata induces hydrofracturing which focuses dewatering solutions. Gold is deposited due to pressure and temperature decrease or local changes in physico - chemico conditions caused by the reaction of fluids with wall rocks (reactive beds in turbidites are predominantly carbonaceous strata). The largest of turbidite - hosted goldfields are confined to back -arc or marginal sea basins with restricted oceanic circulation. The richest concentrations of gold occur proximal to the original source within the greenschist facies formations lowermost in a thick turbidite sequence and exhibit strong combined structural and lithological association. Turbidites represent important strata for the concentration and preservation of gold not only during sedimentation and diagenesis but also during later deformation and metamorphism.
Keywords: Gold ores; Turbidites